Textbook of Aramaic Ostraca from Idumea, volume 2: Dossiers 11-50: 265 Commodity Chits - Porten, Bezalel (Eisenbrauns, 2016)
Since 1991, some 2,000 Aramaic ostraca deriving from the south of Israel have appeared on the antiquities market and are now scattered in 9 museums and libraries and 21 private collections. Of these, the majority are still not formally published, and in this second volume in the series, Bezalel Porten continues the publication of this important corpus of 4th century B.C.E. economic texts. With the expert epigraphic assistance of Ada Yardeni and hand-copies by her as well, Porten here provides the second volume of texts, organized by ""dossier"" based on the primary personage cited in the text